The Relationship between Husband's Support and Pregnant Women's Adaptability - Nugraha, M. Akbar; Keliat, Budi Anna; Mustikasari (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Pregnancy is a life process experienced by women. It leads to physical, mental, and social changes in the mother. Pregnant women need to adapt to these changes throughout pregnancy. This study aims to determine the relationship between husband's support and the adaptability of pregnant women. This is a quantitative study using a descriptive-correlational design with a cross-sectional approach. The sample consisted of 157 pregnant women. Univariate analysis was presented in frequency distribution tables, while bivariate analysis used Pearson’s product-moment correlation. The adaptability of pregnant women in terms of physiological, self-concept, role function, and interdependence, as well as husband’s support, were categorized as good. A significant relationship was found between husband's support and the adaptability of pregnant women, specifically in physiological adaptation (p-value 0.000), self-concept (p-value 0.008), role function (p-value 0.002), and interdependence (p-value 0.000). Husband's support has a significant relationship with pregnant women’s adaptability in terms of physiological adjustment, self-concept, role function, and interdependence. Pregnant women can better adapt to pregnancy-related changes when they receive strong support from their husbands.